Regulation of Doublesex1 Expression for Environmental Sex Determination in the Cladoceran Crustacean Daphnia - Kato, Yasuhiko; Watanabe, Hajime (Frontiers in Cell and Developmental Biology, 2022)
The cladoceran crustacean Daphnia produces only females by parthenogenesis in a healthy population. However, in response to environmental declines such as crowding and lack of foods, it produces eggs destined to become males that are genetically identical to females. During the development of the sexually committed eggs, DM domain-containing transcription factor Doublesex1 (Dsx1) orchestrates male trait formation globally both in somatic and gonadal tissues. Recent studies have revealed that Dsx1 expression is tightly controlled at transcriptional, post-transcriptional, and epigenetic levels to avoid sexual ambiguity. In this review, together with basic information on Dsx1 structure and expression, we introduce the multi-layered Dsx1 regulation and discuss how each regulation is interconnected for controlling male development in environmental sex-determining Daphnia.